2019
DOI: 10.1186/s12870-019-1812-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and functional analysis of 4-Coumarate:CoA ligase 4(4CL-like 1)from Fraxinus mandshurica and its role in abiotic stress tolerance and cell wall synthesis

Abstract: Background Four-Coumarate:CoA ligase gene ( 4CL ) plays multiple important roles in plant growth and development by catalyzing the formation of CoA ester. 4CL belongs to the plant phenylpropane derivative, which is related to the synthesis of flavonoids and lignin and is a key enzyme in the biosynthetic pathway. Results In this study, 12 4CL genes of Fraxinus mandschurica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 65 publications
7
44
0
Order By: Relevance
“…On the other hand, the Gh4CL7 overexpression plants had a lower level of H 2 O 2 and MDA and a higher activity of antioxidant enzymes (SOD, POD, and CAT) compared to WT under the drought stress conditions. These results are consistent with previous finding that Fm4CL had a role in drought tolerance by modulating the level of ROS [24].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…On the other hand, the Gh4CL7 overexpression plants had a lower level of H 2 O 2 and MDA and a higher activity of antioxidant enzymes (SOD, POD, and CAT) compared to WT under the drought stress conditions. These results are consistent with previous finding that Fm4CL had a role in drought tolerance by modulating the level of ROS [24].…”
Section: Discussionsupporting
confidence: 94%
“…We found that repressing the expression level of Gh4CL7 in G. hirsutum reduced the lignin content and led to a reduction in drought resistance, consistent with the result of rice plants with a decreased lignin content being more prone to drought stress [63]. Studies in Fraxinus mandshurica also showed that decreased lignin content resulted in drought resistance reduction [24]. The hydrophobicity of lignin is thought to have an inhibitory effect on the transpiration of plant tissue under drought conditions [64], that could be the reason for Arabidopsis plants overexpressing Gh4CL7 that had an increased level of lignin content being more resistant to drought.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, the KEGG annotation analysis revealed that the expression of a large number of genes related to phenylpropane biosynthesis is upregulated. Some studies have indicated that phenylpropane biosynthesis is related to flavonoid and lignin synthesis, which can improve the osmoregulatory effect of Fraxinus mandshurica [48]. Ma et al reported similar conclusions with respect to buckwheat [49].…”
Section: Flavonoids Are Correlated With Salt Stressmentioning
confidence: 85%
“…4CL belongs to the plant phenylpropane derivative, which is related to the synthesis of avonoids and lignin and is a key enzyme in the biosynthetic pathway. It was reported that Fm4CL-like 1 is involved in secondary cell wall development and lignin synthesis and it play an important role in osmotic stress by affecting cell wall and stomatal development [88]. This may be a part of fungal disease immune response mechanism in G. elata Bl.…”
Section: Discussionmentioning
confidence: 99%